Enhancement of thermoelectric properties by fluorine doping in LaO1−xFxBiPbS3. Issue 1 (January 2019) - Yu, Yi; Wang, Chunchang; Li, Qiuju; Cheng, Chao; Wang, Shuting; Zhang, Changjin
Abstract: The transport and thermoelectric properties of the LaO 1 − x F x BiPbS 3 compounds are studied. On the transport part, fluorine doping effectively reduces the electrical resistivity, and transforms the transport behavior from semiconducting-like to metallic-like. An evident enhancement of thermoelectric performance (power factor) is achieved in LaO 0.6 F 0.4 BiPbS 3, with an obviously larger absolute value of Seebeck coefficient ( | S | ) compared to the parent compound. Hall coefficient measurements reveal the depression of effective carrier density for all the doped samples at high temperatures. The present results suggest that electron carriers alone can not explain the improvement of thermoelectric properties by fluorine doping, the conduction of ionic carriers should be taken into account.